Magnetic Iron Sulfide Nanoparticles as Thrombolytic Agents for Magnetocaloric Therapy and Photothermal Therapy of Thrombosis - Fu, Dapeng; Liu, Junle; Ren, Qilong; Ding, Jinhui; Ding, Heyi; Chen, Xuan; Ge, Xiaohu (Frontiers in Materials, 2019)
Non-invasive removal of thrombosis is a difficult problem in clinical vascular disease. Herein, we reported magnetic hyperthermia combined photothermal therapy for celiac vein thrombosis using Fe3S4 nanoparticles as thrombolytic agents under the stimulation of a near infrared (NIR) laser and an external alternating magnetic field (AMF). Fe3S4 nanoparticles showed excellent magnetothermal conversion performance under the continuous stimulation of an AMF and very good photothermal conversion performance under the irradiation of a NIR laser. Moreover, Fe3S4 nanoparticles exhibited a synergistic thermal conversion effect under the co-stimulation of NIR and AMF. In addition, the Fe3S4 nanoparticles possess the ability for magnetic resonance (MR) imaging with the transverse relaxivity (r2) is up to 53.1 mM−1 s−1. Finally, we, for the first time, proved the Fe3S4 nanoparticles as a promising thrombolytic agent for both photothermal thrombolytic capacity and magnetothermal thrombolytic ability. Our work provides the insight of hyperthermia for removal of the thrombosis.